Analisis Perhitungan Pada UMKM Muncheaps Dengan Metode Variabel Costing Terhadap Harga Pokok Produksi - Yunda Dinar Ferawati; Yunitsa Rakhmawati; Kholida Maula (Peneliti.net, 2023)
It is very important to consider production costs that are directly related to the manufacturing process, such as raw material costs, direct labor costs, and factory overhead costs, when calculating the cost of goods manufactured. Both the selling price and the company's profit margin will be affected by this calculation. Knowing the manufacturing costs in Muncheaps SMEs is the aim of this research. Direct interviews with Muncheaps UMKM owners were used with a descriptive qualitative research type. Based on this, the results of research on Muncheaps SMEs are able to produce goods at a price of IDR 5,385,000 using a variable costing approach. Due to the owner's ignorance to record in making a report on the cost of the product.